Peningkatan Keterampilan Kerajinan Origami Melalui Pelatihan Pada Masyarakat Desa Tanjung Tambak Baru Kecamatan Tanjung Batu - Kurniawan, Kurniawan; Agustian, Wiwin; Irwansyah, Irwansyah; Maryani, Maryani; Nurhayanti, Indah (Jurnal Nasional Pengabdian Masyarakat, 2025)
Community Service (PKM) aims to improve the skills of the Tanjung Tambak Baru Village community in the field of origami-based handicrafts as an alternative to developing the creative economy. Based on initial observations, the community in the village has enough free time, but it has not been used productively. On the other hand, skills in craft arts such as origami are still very limited, even though they have the potential to be developed into products of economic value. This activity was carried out for two months, namely from May to June 2025, through a series of training consisting of an introduction to the basics of origami, practice in making various shapes, to product packaging and an introduction to entrepreneurship. The implementation method includes counseling, direct training, mentoring, and evaluation. The results of the activity showed an increase in participants' skills in making origami crafts, the formation of village craft groups, and the emergence of entrepreneurial interest from some participants. Active community participation and support from the village government are the keys to the success of this activity. This program has a positive impact not only in terms of skills and creativity, but also opens up economic opportunities through the utilization of local craft products. Thus, this origami training can be one of the strategies for sustainable community empowerment